Estimación de la biomasa de la hoja del pejibaye (Bactris gasipaes H.B.K., Palmae) - Clement, Charles R (1990)
Foliar biomass is important for estimating growth parameters for breeding and agronomic studies. Leaf dimensions and weights were measured in three populations of pejibaye mainiained by INPA in Manaus, Amazonas, Brazil, and a method to estimate leaf biomass from rachis dimensions was developed. The linear regression "Lag leaf biomass = 0.97 Lag maximum transversal rectangular area of the rachis" estimated biomass with an error of 2% and is recommended for immediate use with Amazonian populations. Oifferences among populations follow tendencies expected during the domestication process in this species: greater leaf area with less supporting structure (petiole/rachis), permited by thinner, lighter leaflets in the more derived populations.